Diseño y construcción de un sistema de baño turco y sauna para la Universidad Nacional de Loja. - Jaramillo Carrión, Ramiro José (2009)
The end of our Project of Thesis, has the end of to design and to build a SYSTEM OF VAPOR FOR TURKISH BATHROOM AND it STOPS BATHROOM SAUNA IN THE NATIONAL UNIVERSITY DE LOJA, the same that allows to contribute in the formation theoretical practice of the students of the Area of Energy, the Industries and the Natural Resources Not Renewable of the National University of Loja. This system of vapor (generator) has the function of transferring to the water the energy in form of heat of the gases product of the combustible combustion of substances so that becomes vapor and in turn this he/she enters in contact with the body and the benefits are completed for the health of the Turkish bathroom and sauna. The general structure of this investigation is made up of four chapters. The first chapter is approached aspects related with the basic principles of generation of vapor, concepts related with the design construction of the system of vapor for Turkish bathroom and it stops bathroom sauna, and the theoretical sustentation for the project. In the second chapter we are carried out the design, calculation of the system of vapor and we surrender the selection of the materials and the different techniques used in the project is applied and in the last one chapter we surrender, it is analyzed the results, the operation tests, the economic valuation, the environmental impact. Finally the conclusions of the work are obtained and some important aspects are recommended on the thematic one.